Integrated Solar Fuel Generators 2018
DOI: 10.1039/9781788010313-00079
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Composition and Structure on the Oxygen Evolution Reaction (OER) Occurring on NiFeOxCatalysts

Abstract: The use of wind and solar energy to carry out the electrochemical splitting of water is a subject of considerable contemporary interest, since hydrogen produced by this means could be used to store renewable but intermittent electrical energy, to power fuel-cell vehicles, and to hydrodeoxygenate biomass or reduce CO 2 to carbon-containing fuels. 1-5 The challenge, therefore, is to develop energy-efficient systems utilizing renewable sources of electricity to achieve the electrochemical splitting of water. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…In detail, from in operando XAS and density functional theory calculation analysis, the high OER activity is attributable to the substitution of Fe 3+ cations for Ni 3+ cations into the lattice of Ni–Fe-based electrocatalysts. Although the bond length of Fe–O is similar to that of Ni–O, Fe 3+ sites Ni–Fe-based electrocatalysts show significantly superior OER activity than Ni 3+ sites in Ni based- or Ni–Fe-based electrocatalysts and Fe 3+ sites in Fe-based electrocatalysts . The electrocatalytic kinetics of the electrodes toward the OER were investigated using the Tafel plots derived from the corresponding polarization curves in Figure b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, from in operando XAS and density functional theory calculation analysis, the high OER activity is attributable to the substitution of Fe 3+ cations for Ni 3+ cations into the lattice of Ni–Fe-based electrocatalysts. Although the bond length of Fe–O is similar to that of Ni–O, Fe 3+ sites Ni–Fe-based electrocatalysts show significantly superior OER activity than Ni 3+ sites in Ni based- or Ni–Fe-based electrocatalysts and Fe 3+ sites in Fe-based electrocatalysts . The electrocatalytic kinetics of the electrodes toward the OER were investigated using the Tafel plots derived from the corresponding polarization curves in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in good agreement with the previous results stating that Ni and Fe catalysts located on opposite sides of the volcanic plot are attributed to achieve a balanced metal−OH bond strength, 10,36 which is one primary factor determining the OER activity. In detail, from in operando XAS and density functional theory calculation analysis, the high OER activity is attributable to the substitution of Fe 3+ cations for Ni 3+ 37 The electrocatalytic kinetics of the electrodes toward the OER were investigated using the Tafel plots derived from the corresponding polarization curves in Figure 4b. The Tafel slope was fitted by the Tafel equation: η = b log j + a (where η represents the overpotential, b is the Tafel slope, and j represents the current density).…”
Section: Electrochemical Characteristicsmentioning
confidence: 99%
“…21 By conducting in situ Raman spectroscopy, Bell and co-workers demonstrated that Fe efficiently boosts the catalytic activity of NiOOH. 58 Friebel et al proved this effect of Fe using operando X-ray absorption spectroscopy and density functional theory (DFT) calculations. 59 Concerted efforts by various groups have been dedicated to the study of NiFe based OER catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…13,28,32,49) Based on the results presented in the aforementioned studies, it became apparent that the OER activities of NiFe hydroxides are strongly affected by the Ni/Fe atomic ratio. 18,22,28,[49][50][51][52] However, the other constituent elements of austenitic SS, including Cr, Mn and Mo, are easily eluted into the electrolyte under AWE conditions; therefore, such elements do not contribute to enhancing the OER activity of the SCL.…”
Section: Origin Of the High Oer Activity Of The Surface Catalyst Laye...mentioning
confidence: 99%